Crossing the digital divide: ICT implementation in the Al-Ula District - Albalawi, Fahad (Technium Social Sciences Journal, 2021)
This study investigated the use of information and communication technology (ICT) within the Al-Ula school district of Saudi Arabia. Participants for this study were teachers and principals in the Al-Ula school district who had experience using ICT within their schools. Data consisted of interviews with these participants, which were analyzed qualitatively. The central question of this study was: What do teachers and principals identify as the challenges to implementing educational technology in Al-Ula schools? Findings showed multiple barriers to ICT implementation at the organizational, practical/material, and individual level, including a lack of resources, training, policy, and plan for ICT implementation.